LEUKOCYTES DIFFERENTIATION PROFIL OF TILAPIA (Oreochromis niloticus) THAT WERE INFECTED BY ECTOPARASITES IN POND IN SIMPANG TIGA SUB-DISTRICT PEKANBARU - Roslina '; Henni Syawal; Morina Riauwaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis research was conducted in Oktober to Desember 2015 in the Laboratory of Parasite and Fish Disease of Fisheries and Marine Science Faculty, University of Riau. This study aims to understand the leukocytes differentiation Profil of tilapia (Oreochromis niloticus) that were infected by ectoparasites in Simpang Tiga sub-district Pekanbaru. The research method used in this study is a survey method by taking sampels in the field and fish sample will be analized in the laboratory, and will be identificied based on Kabata, 1995. The hematologycal parameter (leukocytes differentiation) will be measured based on Swicki and Anderson, 1974. The result shown that three types of ectoparasite that were infected in tilapia was Trichodina sp., Dactylogyrus sp., and Gyrodactylus sp. The total leukocytes of male tilapia was 92.350-103.400 cells/mm3 and famale tilapia was 89.375-100.200 cells/mm3. Differentiation of leukocytes such as lymphocytes of male tilapia was 65-73,5%, whereas the famale tilapia was 61,5-77,5%, monocytes of male tilapia was 22-31,5%, whereas the famale tilapia was 18-34,5%, and neutrophils of male tilapia (3-4,5%) was higher than famale tilapia (4-5%).Keywords : Ectoparasites, Differentiation, Leukocytes, Tilapia, Pekanbaru